Нові рівняння інфінітезимальних деформацій поверхонь в E₃ - Потапенко, І.В. (Український математичний журнал, 2010)
Доказано необходимое и достаточное условие, которому должны удовлетворять два симметрических тензорных поля для существования вектора смещения при инфинитезимальной деформации поверхности в евклидовом пространстве E₃. We establish a condition for two symmetric tensor fields that is necessary and sufficient for the existence of a displacement vector in the case of infinitesimal deformation of a surface in the Euclidean space E₃.